Web design for dyslexics: Accessibility of Arabic content - Al-Wabil, Areej; Zaphiris, Panayiotis; Wilson, Stephanie (My University, 2006)
This paper reports results of a workshop on the design of electronic content for users with Specific Learning Difficulties (SpLD), particularly Arabic dyslexics. First we shed some light on the nature of the Arabic language and discuss features that account for the unique needs of Arabic users with reading disorders. Then we present recommendations for accessible web design for Arabic content in light of existing guidelines on web design for dyslexic users.